"The Cult of the Diva" – Rufus Wainwright as Opera Queen - Smith, Oliver C. E. (Transposition. Musique et Sciences Sociales, 2013)
The music of Rufus Wainwright has been afforded much critical acclaim thanks to the singer-songwriter’s understanding of Queer cultural history, and the candor with which he explores (homo)sexuality in his music. This case study seeks to examine his use of opera in particular, and how Wainwright uses the historical trope of the opera queen to incorporate his own queerness into music, thus asserting an authority of difference and challenging the dominant (hetero)norm constructions of masculinity in popular music. Wainwright disregards any cultural framework imposed by heternormativism, and reclaims the Orphic figure of operatic authority as one of queer power through this absence. By drawing on his own relationship with opera, Wainwright exploits the right this gives him by reinterpreting cultural history, and revising the pejorative stereotype that is an opera queen.
Number: 3 Publisher: Association Transpositon. Musique et Sciences Sociales
Keywords: Eurydice; Hallelujah; Jeff Buckley; Memphis Skyline; Rufus Wainwright; Waiting For A Dream; Want Two; diva; gay; heteronormativism; identity; masculinity; opera; queer; stereotype

True Loves, Dark Nights: Queer Performativity and Grieving Through Music in the Work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)

Montréal Rave: An Oral History - Borzeix, Olivier (Red Bull Music Academy, 2016)
Tiga, Christian Pronovost, Jeff Waye and more remember the golden era of raves in Montréal.

Robert Ouimet and Pierre Gagnon - Burns, Todd L. (Redd Bull Music Academy, 2016)
Explore the Red Bull Music Academy archive, tracing the global music institution’s more than 20-year history

Queer Perspectives in New Music - Dharmoo, Gabriel; Brosin, Annette; R. Green, Anthony; Nickel, Luke; Doolittle, Emily; Henry, Symon; Kasahara 笠原 貞野, Teiya (Circuit: Musiques contemporaines, 2021)

On feeling mighty real: devenir gay à Montréal pendant l’ère disco dans Funkytown, de Daniel Roby - Foerster, Maxime (Contemporary French Civilization, 2018)
Our catalogue of journals

Nightclubbing: Montréal’s Lime Light - Pemberton, Rollie (Red Bull Music Academy, 2016)
The Lime Light and its innovative DJ Robert Ouimet made Montreal a disco city during the ’70s. This is the club's story.